The Impact of the COVID-19 Omicron Variant on Immunocompromised Patients: ICU Admissions and Increased Mortality - Jan Pander; Fabian Termorshuizen; Dylan W. de Lange; Wendy Beekman-Hendriks; Josien Lanfermeijer; Ferishta Bakhshi-Raiez; Dave A. Dongelmans (Infectious Diseases and Therapy)
Abstract Introduction The corona virus disease 19 (COVID-19) pandemic has presented a global health challenge, and several consecutive variants of the severe acute respiratory syndrome–corona virus-2 (SARS-CoV-2) virus have been dominant. Previous studies highlighted decreased mortality rates during the predominance of the omicron variant; however, severely immunocompromised individuals remained at high risk due to limited vaccine response. This study aims to compare mortality rates during the omicron period between immunocompromised and non-immunocompromised patients in intensive care units (ICUs) in The Netherlands. Methods Utilizing data from the Dutch National Intensive Care Evaluation (NICE) registry, this study analyzed ICU admissions due to COVID-19 from February 2022 to December 2023. Patients were categorized as immunocompromised based on recorded immunologic insufficiencies or associated conditions. A historical cohort of viral pneumonia patients from 2017 to 2019 was used for comparison. Logistic regression analyses, adjusted for age, gender, body-mass index (BMI), and acute physiology and chronic health evaluation IV (APACHE-IV) mortality risk, compared in-hospital and ICU mortality and length of stay between groups. A sensitivity analysis excluded early omicron period admissions to assess the consistency of findings. Results Among 1491 patients admitted to the ICU due to COVID-19, 29.5% were immunocompromised, showing significantly higher in-hospital adjusted odds ratio (ORadj = 1.56, 95% CI 1.20–2.04) and ICU mortality (ORadj = 1.64, 95% CI 1.25–2.17) compared to non-immunocompromised patients. The historical cohort exhibited lower mortality rates for immunocompromised individuals compared to the COVID-19 cohort. Sensitivity analysis confirmed these trends, with slight attenuation of odds ratios. Conclusion Immunocompromised patients admitted to the ICU due to COVID-19 during the omicron period had higher mortality than non-immunocompromised patients. Additionally, immunocompromised patients with COVID-19 had higher mortality than immunocompromised patients with other viral pneumonias. Our results provide additional evidence that COVID-19 is still a significant health concern to immunocompromised individuals, which warrants specific and effective measures to protect this vulnerable group.